2009
DOI: 10.1111/j.1478-5153.2009.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hyperglycaemia of diabetic patients undergoing cardiac surgery – a clinical audit

Abstract: More consistent blood glucose testing might be achieved through the use of evidence-based protocols. However, the education of staff is as important as it develops knowledge on the complex metabolic interactions of diabetic patients undergoing cardiac surgery. While this means investing in staff education and policy development, costs for daily care and expensive treatments for complications will be saved as patient recovery will be speedier and less eventful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
1
3
0
2
Order By: Relevance
“…We demonstrate that ideal glycemic control is very di cult to attain in patients with elevated HbA1c. As reported by Lehwaldt et al [12], BSL values appear to peak on the second postoperative day; however, we add to current literature by also demonstrating that the decline after the peak depends upon preoperative HbA1c. We have demonstrated that in patients with HbA1c > 10%, postoperative BSL levels actually peak on the 3 rd postoperative day after which it declines.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We demonstrate that ideal glycemic control is very di cult to attain in patients with elevated HbA1c. As reported by Lehwaldt et al [12], BSL values appear to peak on the second postoperative day; however, we add to current literature by also demonstrating that the decline after the peak depends upon preoperative HbA1c. We have demonstrated that in patients with HbA1c > 10%, postoperative BSL levels actually peak on the 3 rd postoperative day after which it declines.…”
Section: Discussionsupporting
confidence: 78%
“…They report 10% readings of BSL > 200 mg/dl with HbA1c > 6.5 %. Lehwaldt et al [12] audited 150 patients with diabetes mellitus undergoing cardiac surgery in a single center in UK. They report that at least 32%, 24% and 34% readings were above 180 mg/dl (> 10 mmol/lit).…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing surgery with hyperglycemia due to type 2 diabetes mellitus (DM) are more susceptible to hospital-acquired infection [3]. In recent years, clinical trials and studies evaluated that blood glucose level control in preoperative patients significantly decreases mortality and morbidity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Já no segundo estudo, os resultados evidenciaram que a administração de insulina glargina e glulisina manteve de forma mais efetiva o controle glicêmico, reduzindo as complicações no PO como ISC, pneumonia e bacteremia (19) . (20) .…”
unclassified
“…A conclusão da pesquisa apontou que o controle rigoroso da glicose por meio de protocolo de infusão de insulina IV, no pós-operatório, diminui significativamente a incidência de infecção da ferida cirúrgica na amostra com diabetes (36) . recomendaram o controle glicêmico no perioperatório para a prevenção deste tipo de infecção (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)22,(24)(25)(26)(27)(29)(30)(31)(32)(33)(34)(35)(36) .…”
unclassified